Adding evidence of the effects of treatments into relevant Wikipedia pages: a randomised trial - Adams, Clive E; Montgomery, Alan A; Aburrow, Tony; Bloomfield, Sophie; Briley, Paul M; Carew, Ebun; Chatterjee-Woolman, Suravi; Feddah, Ghalia; Friedel, Johannes; Gibbard, Josh; Haynes, Euan; Hussein, Mohsin; et al. (2020)
Objectives To investigate the effects of adding high-grade quantitative evidence of outcomes of treatments into relevant Wikipedia pages on further information-seeking behaviour by the use of routinely collected data.